1989
DOI: 10.1093/clinchem/35.12.2277
|View full text |Cite
|
Sign up to set email alerts
|

Studies on methylmalonic acid in humans. II. Relationship between concentrations in serum and urinary excretion, and the correlation between serum cobalamin and accumulation of methylmalonic acid.

Abstract: Methylmalonic acid (MMA) concentrations are increased in cobalamin (vitamin B12) deficiency, but the relative diagnostic usefulness of determination of MMA in serum vs urine has not yet been assessed. We obtained urine collections and matched serum samples from 28 healthy volunteers and from 20 consecutive patients admitted for clinical and hematological evaluation because of low cobalamin concentrations in serum. Increased concentrations of MMA in serum were found in 12 patients, in all of whom a clinical dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Although there are no data on renal clearance of circulating MMA in cats, it has been shown that urinary excretion of serum MMA relative to that of creatinine was <1 in human patients. 15,[31][32][33] It was proposed that an unknown percentage of serum MMA is not excreted by the kidney, but instead is metabolized via unknown pathways. [31][32][33] If this theory is valid and applicable to cats, individual differences in metabolism might have affected urinary excretion of MMA, which would explain the discrepancy in serum and urine MMA concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are no data on renal clearance of circulating MMA in cats, it has been shown that urinary excretion of serum MMA relative to that of creatinine was <1 in human patients. 15,[31][32][33] It was proposed that an unknown percentage of serum MMA is not excreted by the kidney, but instead is metabolized via unknown pathways. [31][32][33] If this theory is valid and applicable to cats, individual differences in metabolism might have affected urinary excretion of MMA, which would explain the discrepancy in serum and urine MMA concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…6,[12][13][14] In humans, a linear relationship exists between serum and urine MMA concentrations. 15 In veterinary medicine, comparisons between serum and urine MMA concentrations are lacking.…”
mentioning
confidence: 99%
“…Plasma tHcy, as well as methylmalonic acid in serum and urine (Rasmussen et al, 1989), have been demonstrated to be sensitive markers of intracellular folate and cobalamin de®ciency (Allen et al, 1990). tHcy was measured and found signi®cantly high in anorexia patients.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective review of the medical records of all ambulatory, community‐dwelling adults evaluated by the author in an internal medicine clinic at a university‐based staff model health maintenance organization for possible cobalamin deficiency between August 1, 1993, and June 30, 2005, in whom concurrent cobalamin, serum folate, and MMA levels were obtained was conducted as previously described . Because both renal insufficiency and diabetes mellitus increase MMA and homocysteine levels, individuals were excluded if renal function was impaired (serum creatinine levels >1.5 mg/dL in men, >1.3 mg/dL in women) or if diabetes mellitus was present . Ten individuals with cobalamin levels below the reference range (≤200 pg/mL) and six with cobalamin levels above the reference range (>1,100 pg/mL) were also excluded from analysis.…”
Section: Methodsmentioning
confidence: 99%